2015
DOI: 10.1002/anie.201507894
|View full text |Cite
|
Sign up to set email alerts
|

High‐Resolution Crystal Structure of a Silver(I)–RNA Hybrid Duplex Containing Watson–Crick‐like CSilver(I)C Metallo‐Base Pairs

Abstract: Metallo-base pairs have been extensively studied for applications in nucleic acid-based nanodevices and genetic code expansion. Metallo-base pairs composed of natural nucleobases are attractive because nanodevices containing natural metallo-base pairs can be easily prepared from commercially available sources. Previously, we have reported a crystal structure of a DNA duplex containing T-Hg(II)-T base pairs. Herein, we have determined a high-resolution crystal structure of the second natural metallo-base pair b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
81
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(83 citation statements)
references
References 88 publications
2
81
0
Order By: Relevance
“…The DNA1–Hg II represents the first DNA structure carrying the C–Hg II –T pairs to date; it reveals that the exocyclic N4 atom can also interact with the Hg II ion. Though we failed to capture it in our study, the structure of the RNA duplex carrying the C–Ag I –C pair suggested that the N3 atom of the C residue has the potential to coordinate with the Hg II ion (32). Together, these observations advanced our understanding on the Hg II -mediated metallo-base pairs.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…The DNA1–Hg II represents the first DNA structure carrying the C–Hg II –T pairs to date; it reveals that the exocyclic N4 atom can also interact with the Hg II ion. Though we failed to capture it in our study, the structure of the RNA duplex carrying the C–Ag I –C pair suggested that the N3 atom of the C residue has the potential to coordinate with the Hg II ion (32). Together, these observations advanced our understanding on the Hg II -mediated metallo-base pairs.…”
Section: Discussionmentioning
confidence: 88%
“…In the reported 12TT DNA structure (33) and the C–Ag I –C pair containing RNA structure (32), the metallo-base pairs are mainly stabilized by the N3–Hg II –N3 and N3–Ag I –N3 interactions, respectively. Interestingly, besides the Hg II -mediated interactions, we observed that the conformation of the C3–T6* pair is also stabilized by one water molecule located at the minor grove of the DNA1–Hg II structure (Figure 2B).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…thymine (T) and cytosine (C)) are known to form an Hg(II)-or Ag(I)-mediated base pair, in which N3 atoms coordinate to the metal ion (i.e. T-Hg(II)-T [8][9][10][11] or C-Ag(I)-C [12,13], respectively). A variety of artificial ligand-type nucleobases have been developed so as to form metal-mediated base pairs with various metal ions including Mn(II), Ni(II), Cu(II), Pd(II), or Ag(I) ions [1].…”
Section: Introductionmentioning
confidence: 99%